Polarity affects the antioxidant and antimicrobial activities of jellyfish Acromitus hardenbergi extracts - Khong, Nicholas M. H.; Foo, Su Chern; Yau, Sook Kun; Chan, Kim Wei; Md. Yusoff, Fatimah (Korean Society of Fisheries and Aquatic Sciences, 2022)
Jellyfish is an emerging aquaculture species, farmed for Oriental cuisines and nutraceutical ingredients. This study aimed to examine antioxidative and antimicrobial potentials of various fractions of the jellyfish, Acromitus hardenbergi. The bell and oral arms of the jellyfish were sequentially extracted with petroleum ether (PE), dichloromethane (DCM), chloroform (CHCl3), methanol (MeOH), and water (H2O) to extract its bioactive in an increasing polarity gradient. Test fractions were assayed for antiradical activities using electron spin resonance spectrometry, β-carotene-linoleate model and Folin-Ciocalteu assay; and antimicrobial activity against 2 Gram-negative bacteria, 4 Gram-positive bacteria and 2 fungal species using the disc diffusion assay. All fractions were also subjected to Fourier Transform Infrared (FTIR) analysis to identify types of functional groups present. It was found that the hydrophilic extracts (H2O fractions) possessed the most effective radical scavenging activity (p < 0.05) while the lipophilic extracts (PE fractions) the most active antimicrobial activity, especially against Gram-positive bacteria (p < 0.05). Total oxidation substrates content was found to be highest in the PE fractions of jellyfish bell and oral arms (p < 0.05). FTIR data showed that the H2O and MeOH fractions contains similar functional groups including -OH, -C=O, -N-H and -S=O groups, while the PE, DCM, and CHCl3 fractions, the -CH3, -COOH groups. This study showed that A. hardenbergi contains antioxidants and antimicrobials, thereby supporting the traditional claim of the jellyfish as an anti-aging and health-promoting functional food. Bioassay-guided fractionation approach serves as a critical milestone for the strategic screening, purification, and elucidation of therapeutically significant actives from jellyfish.